Green Human Resource Management and Sustainable Performance With the Mediating Role of Green Innovation: A Perspective of New Technological Era - Awwad Al-Shammari, Awwad Saad; Alshammrei, Shaher; Nawaz, Nishad; Tayyab, Muhammad (Frontiers in Environmental Science, 2022)
The purpose of this study is to investigate the relationship between green human resource management bundle practises and green innovation, as well as their impact on sustainability performance as measured by the Triple Bottom Lines (i.e. environmental, social, and economic performance). It is decided to use a quantitative approach in order to collect data from 335 small and medium-sized (SMEs) businesses operating in the Kingdom of Saudi Arabia, through a customized survey. Structure equation modelling was applied through smart-PLS to analyse the collected data. Results show that green human resource management bundle practices have positive and significant impact on sustainable performance of SMEs. Furthermore, results indicate that green innovation has significant impact on sustainable performance as well as green innovation partially mediates the relationship between green human resource practices and sustainable performance of SMEs. This study demonstrates that the implementation of GI by firms can be enhanced through the use of GHRM, which, in turn, would enhance firms' sustainability. Additionally, this study both confirms and enhances the traditional understanding. The study also depicts that environmental management practices in the human resource and innovation sectors can result in greater sustainability.